Enhanced electrocatalytic activity of gold nanoparticles on hydroxyapatite nanorods for sensitive hydrazine sensors. Issue 17 (11th April 2016) - Bharath, G.; Naldoni, Alberto; Ramsait, K. Hasini; Abdel-Wahab, Ahmed; Madhu, Rajesh; Alsharaeh, Edreese; Ponpandian, N.
Abstract : With the synthesized Au/hydroxyapatite (HAp) nanocomposites, the HAp nanorods favored adsorption of hydrazine, thus bringing hydrazine closer to the catalytic sites of Au nanoparticles and increasing the efficiency of hydrazine oxidation. Abstract : Well-designed noble metals and ceramic nanoarchitectures are significantly important for the development of high performance, selective, sensitive and cost effective electrochemical sensors. Here, we report gold (Au) nanoparticles (NPs) uniformly dispersed on hydroxyapatite (HAp) nanorods forming particles on rod nanoarchitectures for sensitive hydrazine sensors. The Au/HAp nanocomposites were prepared by a versatile hydrothermal precipitation method. The precipitated citrate-stabilized Au NPs were 6–8 nm in size and strongly anchored onto rod-shaped HAp with a diameter of 10 nm and length of 65 nm. The structural, chemical, and electrochemical properties and growth mechanism of the Au nanoparticles on the HAp nanorods (NRs) are presented. Progress toward the application of hybrid nanocomposites in electrochemical oxidation of hydrazine is reviewed. Compared to Au NPs, the incorporation of Au NPs into HAp NRs favored the adsorption of hydrazine, thus bringing hydrazine much closer to the catalytic sites of Au NPs and then increasing the efficiency of hydrazine oxidation in neutral solution. The amperometric ( i – t ) hydrazine sensor, using the as-prepared Au/HAp as the electrochemical catalyst, shows a wide linear response range of 0.5–1429 μM, a lower detection limit (0.017 μM) and very high sensitivity of 0.5 μA μM −1 cm −2 . Furthermore, the Au/HAp nanocomposites showed an excellent anti-interference property towards the various organic and inorganic electroactive compounds, and good inter-electrode and intra-electrode reproducibility. Our present technique shows both qualitative and quantitative measurement of hydrazine in various water samples with high sensitivity, cost effectiveness and rapid analysis time.